2016
DOI: 10.1021/acs.macromol.6b01512
|View full text |Cite
|
Sign up to set email alerts
|

“One-Pot” Aminolysis/Thiol–Maleimide End-Group Functionalization of RAFT Polymers: Identifying and Preventing Michael Addition Side Reactions

Abstract: We show that many of the nucleophiles (catalysts, reducing agents, amines, thiols) present during “one-pot” aminolysis/thiol–maleimide end-group functionalization of RAFT polymers can promote side reactions that substantially reduce polymer end-group functionalization efficiencies. The nucleophilic catalyst 1,8-diazabicyclo[5.4.0]­undec-7-ene and the reducing agent tributyl­phosphine were shown to initiate anionic polymerization of N-methyl­maleimide (NMM) in both polar and nonpolar solvents whereas hexylamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…[65,83] Functionality is then introduced by thiol-ene, thiol-yne, Michael,a nd maleimide reactions either as as eparater eaction step or in ao ne-pot process. [18,19,86,87] In analogy to ATRP,s trategies for directedt hiol transformations in RAFT polymerization are mediated by the MTS [41] and PDS group (Scheme 2B). [45] Both moieties can be introduced by aminolysis of the thiocarbonylthio end-group as ap ostpolymerization modification and, after directed disulfide formation, were utilized in encapsulation of gold nanoparticles, [88] protein-polymer conjugates [89] and drug attachment by disulfides.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[65,83] Functionality is then introduced by thiol-ene, thiol-yne, Michael,a nd maleimide reactions either as as eparater eaction step or in ao ne-pot process. [18,19,86,87] In analogy to ATRP,s trategies for directedt hiol transformations in RAFT polymerization are mediated by the MTS [41] and PDS group (Scheme 2B). [45] Both moieties can be introduced by aminolysis of the thiocarbonylthio end-group as ap ostpolymerization modification and, after directed disulfide formation, were utilized in encapsulation of gold nanoparticles, [88] protein-polymer conjugates [89] and drug attachment by disulfides.…”
Section: Structurementioning
confidence: 99%
“…Thus, many end‐group transformation methods involve the free thiol, which is obtained by reduction or through reaction with nucleophiles for example, aminolysis . Functionality is then introduced by thiol‐ene, thiol‐yne, Michael, and maleimide reactions either as a separate reaction step or in a one‐pot process …”
Section: Controlled Radical Polymerization (Crp)mentioning
confidence: 99%
“…Second, RAFT polymerization method has emerged as the versatile and most attractive living radical polymerization technique for biomedical material research which can afford well‐defined controlled polymers, most of all the opportunity to generate the corresponding polymeric thiols . Therefore, the unique combination of RAFT techniques with thiol‐based coupling reaction via tandem reactions in a one‐pot synthesis can be considered as an appealing synthetic strategy to explicitly fabricate polymer conjugates for biology . The used synthetic methodology commenced with the direct ligation of an alpha‐carbonyl‐bromo group, carrying the peptidic residue to the RAFT made thermoresponsive controlled polymers in a one‐pot reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Abel and McCormick on the RAFT polymerization of methacrylamides has shown that livingness through preservation of the trithiocarbonate end‐group can be achieved by utilizing acidic solutions, which protonate nucleophilic sites (including the N atom of the amide) . This led to the addition of 1.15 equivalents of HCl to the chain extension of poly(DMA) 41 , which gave poly(DMA) 41 ‐ b ‐( 1b ) 97 in 97% conversion with excellent control/living character as demonstrated by narrow MWD ( M w / M n = 1.22) with M n close to M n,th [Fig.…”
Section: Introductionmentioning
confidence: 99%